AIM2 Inflammasome's First Decade of Discovery: Focus on Oral Diseases - Wang, Lufei; Sun, Lu; Byrd, Kevin M.; Ko, Ching-Chang; Zhao, Zhenxing; Fang, Jie (Frontiers in Immunology, 2020)
A common feature of many acute and chronic oral diseases is microbial-induced inflammation. Innate immune responses are the first line of defense against pathogenic microorganisms and are initiated by pattern recognition receptors (PRR) that specifically recognize pathogen-associated molecular patterns and danger-associated molecular patterns. The activation of certain PRRs can lead to the assembly of macromolecular oligomers termed inflammasomes, which are responsible for pro-inflammatory cytokine maturation and secretion, and thus activate host inflammatory responses. About ten years ago, the absent in melanoma 2 (AIM2), was independently discovered by four research groups, and among the “canonical” inflammasomes (including AIM2, NLRP1, NLRP3, NAIP/NLRC4, and pyrin), AIM2 so far is the only one that simultaneously acts as a cytosolic DNA sensor due to its DNA-binding ability. Undoubtedly, such a double-faceted role gives AIM2 greater mission and more potential in the mediation of innate immune responses. Therefore, AIM2 has garnered much attention from the broad scientific community during its first 10 years of discovery (2009-2019). How the AIM2 inflammasome is related to oral diseases has aroused debate over the past few years and is under active investigation. AIM2 inflammasome may potentially be a key link between oral diseases and innate immunity. In this review, we highlight the current knowledge of the AIM2 inflammasome and its critical role in the pathogenesis of various oral diseases, which might offer future possibilities for disease prevention and targeted therapy utilizing this continued understanding.